NUMERACY FOR STEM EDUCATION: TRENDS AND EFFECTIVE PRACTICES - Adi Asmara; Ristontowi; Winda Ramadianti (Review of International Journal Education and School Leadership, 2025)
Numeracy is an essential component in STEM (Science, Technology, Engineering and Maths) education that supports students' critical and analytical thinking skills. Research reveals that high numeracy skills are closely related to success in learning and applying STEM concepts. Current trends in STEM education emphasise an interdisciplinary approach, where theory is combined with real-world applications through methods such as problem-based learning and the use of educational technology. Effective practices in numeracy teaching involve collaboration, communication, and innovation development, and emphasise the importance of equal access to education for all students. The implementation of this strategy is expected to build a young generation that is capable of facing global challenges in the technological era.